2004
DOI: 10.1128/iai.72.12.7306-7310.2004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Translational Fusion of the MrpH Fimbrial Adhesin-Binding Domain with the Cholera Toxin A2 Domain, Coexpressed with the Cholera Toxin B Subunit, as an Intranasal Vaccine To Prevent Experimental Urinary Tract Infection byProteus mirabilis

Abstract: This is a follow-up to our previous study using an intranasal vaccine composed of MrpH, the tip adhesin of the MR/P fimbria, and cholera toxin to prevent urinary tract infection by Proteus mirabilis (X. Li, C. V. Lockatell, D. E. Johnson, M. C. Lane, J. W. Warren, and H. L. Mobley, Infect. Immun. 72:66-75, 2004). Here, we have expressed a cholera toxin-like chimera in which the MrpH adhesin-binding domain (residues 23 to 157) replaces the cholera toxin A1 ADP-ribosyltransferase domain. This chimera, when admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 12 publications
(14 reference statements)
3
39
0
Order By: Relevance
“…Lastly, this report supports the hypothesis that the humoral and cellular responses induced by IsdA-CTA 2 /B are superior to those stimulated by a mixed preparation of antigen and adjuvant (IsdA plus CTA 2 /B). Thus, the structure of the IsdA-CTA 2 /B chimera is optimal for the induction of antigen-specific humoral responses and potentially for presentation on MHC molecules, which is consistent with previous reports of chimeric molecules using distinct antigens (18,36,51). CT and the closely related LTI are gold-standard mucosal adjuvants with a long history of use in animals and more recent use of nontoxic derivatives in humans.…”
Section: Discussionsupporting
confidence: 79%
“…Lastly, this report supports the hypothesis that the humoral and cellular responses induced by IsdA-CTA 2 /B are superior to those stimulated by a mixed preparation of antigen and adjuvant (IsdA plus CTA 2 /B). Thus, the structure of the IsdA-CTA 2 /B chimera is optimal for the induction of antigen-specific humoral responses and potentially for presentation on MHC molecules, which is consistent with previous reports of chimeric molecules using distinct antigens (18,36,51). CT and the closely related LTI are gold-standard mucosal adjuvants with a long history of use in animals and more recent use of nontoxic derivatives in humans.…”
Section: Discussionsupporting
confidence: 79%
“…Vaccination with the adhesin capping the MR/P pilus from P. mirabilis was found to significantly reduce bladder bacterial burdens compared to unvaccinated controls (205). Additionally, vaccination with the pilus adhesin EbpA from E. faecalis reduced the bladder bacterial burden 1,000 times, representing a significant amount of protection against infection (82).…”
Section: Vaccines For Urinary Tract Infectionsmentioning
confidence: 95%
“…The subunit chimeras complex with Ctb pentamers and result in the production of robust and protective immune responses to A2-fused antigens [23][24][25][26][27][28][29]. We focused our efforts on two Tbp-specific domains, the NB domain from TbpB and the L2 domain from TbpA based largely on surface exposure and strain-to-strain sequence conservation.…”
Section: Discussionmentioning
confidence: 99%
“…The non-toxic A2 domain of CtA passes through the central pore of the B subunit which allows for the tethering of the activity domain to Ctb [21]. Previous investigators have demonstrated that the replacement of the toxic A1 moiety of CtA with heterologous proteins genetically fused with the A2 subunit, allowed for production of holotoxin-like chimeras [23][24][25][26][27][28][29]. Employing this approach for TbpA, we focused on the surface-exposed loop 2 (L2).…”
Section: Introductionmentioning
confidence: 99%